Development of guidelines to improve the quality of the choice on termination of pregnancy services in public health facilities in the Tshwane district in Gauteng province - Mulaudzi, Fhumulani Mavis (University of Pretoria, 2018)
The development of guidelines to improve the quality of CTOP services in public health facilities remains very important in ensuring the continuous provision of quality CTOP services. The assessment of the quality of CTOP services in public health facilities has been seriously neglected. The objectives of the study were to assess, determine and evaluate the quality of CTOP services in public health facilities using the Donabedian model of quality care. The purpose of the study was to develop guidelines to improve the quality of CTOP services in public health facilities. A quantitative, non-experimental, cross-sectional survey research design was used to achieve the objectives of the study. The study was conducted in two phases. During the first phase, the objectives of the study were to assess, determine and evaluate the quality of CTOP services in public health facilities using the Donabedian model of quality care. Quantitative data was collected from 104 participants comprising of facility and quality managers, registered professional nurses and midwives and the post-CTOP clients from the eight public health facilities involved in the study. Questionnaires were used to collect data. The findings confirmed the challenges experienced by healthcare professionals and clients in the CTOP clinics. The study revealed the inadequate infrastructural challenges, lack of ablution facilities, lack of rest rooms for clients post termination of pregnancy, lack of privacy, overcrowding of clients, clients not honoring follow up dates, lack of proper referral routes and repeat CTOP requests. In the second phase, guidelines to improve the quality of CTOP services in public health facilities were developed based on the findings of phase one. Modified Delphi technique method was used to develop and refine the guidelines to improve the quality of CTOP services in public health facilities. Three rounds were used to finalize the guidelines by a panel of six experts involved in CTOP and reproductive health services. Further research using other models of quality care is recommended.